2018
DOI: 10.3390/ijerph15020212
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Childhood Health Status on Adult Health in China

Abstract: Childhood health in China was poor in the 1950s and 1960s because of limited nutrition. In the last three decades, China has distinguished itself through its tremendous economic growth and improvements in health and nutrition. However, prior to such growth, access to good nutrition was more variable, with potentially important implications, not only for childhood health, but also for adult health, because of its long-term effects lasting into adulthood. To shed light on these issues, this study examined the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Exposure to disadvantaged childhood SES may have shaped the life-course health trajectories of Chinese adults in different ways 25 , 41 . The following were observed in Chinese adults: disadvantaged childhood SES increased the risk of cognitive disorders 40 and depression 26 ; disadvantaged childhood health significantly predicted cognitive and physical impairment 42 ; and childhood food shortage was associated with late-life glucose abnormalities 23 .…”
Section: Introductionmentioning
confidence: 97%
“…Exposure to disadvantaged childhood SES may have shaped the life-course health trajectories of Chinese adults in different ways 25 , 41 . The following were observed in Chinese adults: disadvantaged childhood SES increased the risk of cognitive disorders 40 and depression 26 ; disadvantaged childhood health significantly predicted cognitive and physical impairment 42 ; and childhood food shortage was associated with late-life glucose abnormalities 23 .…”
Section: Introductionmentioning
confidence: 97%
“…Childhood adversity has also been shown to be related to cognition (e.g., immediate memory, visuospatial construction, language, and delayed memory abilities) [18,19] and some research has even suggested that childhood abuse can be associated with better global cognition, memory, executive function, and processing speeds [20]. Childhood health is likely a robust indicator for orientation, word recall, and backward counting in later life [21][22][23]. Previous research has suggested that exposure to adverse ELCs was associated with increased anxiety levels and cognitive impairment as these variables disrupt the maturation of underlying brain networks [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…There are no existing studies on direct assessment of the effect of the Great Chinese Famine exposure in early life on physical function in middle age. However, a recent study explained that a good childhood health status increases the probability of better adult physical function by 14% (95% CI 12% to 17%) 2912.…”
Section: Discussionmentioning
confidence: 99%